PADME, Benin : Scaling Up a Successful Pilot - McDonald, Jennifer (World Bank, Washington, DC, 2012)
On the surface, PADME (Projet d'Appui au Developpement des Micro-Entreprises) is one of the most profitable African micro-finance institutions (MFIs) that report to the bulletin. Although this profitability is partly due to low cost funds and under-investment in management and operating systems, in the five years since its creation, PADME has built an efficient operation with solid growth in outreach. It serves predominantly women petty traders in two urban centers in Benin, with loans averaging US$400. PADME was created as a project in 1993 by the government of Benin, with funding from the World Bank. Initially, it was part of a broader initiative to offset the social effects of a structural adjustment package. The program's vision was to provide business credit to a broad base of clients, serving those who could not access traditional bank financing. PADME differs from many African institutions because it does not focus specifically on serving the very poor. In this respect, it more closely resembles many Latin American microfinance institutions.